FACE-SAVING FOR TRANSFORMATIONAL LEADERSHIP IN EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Fauzi, Khabib; Akhmad (English Language Teaching Journal, 2024)
The research is dedicated to figure out the application of face-saving oleh transformational leadership dalam dunia pendidikan and to know the strategies of face-saving used by transformational leadership dalam dunia pendidikan di Indonesia. Hal ini menjadi penting dilakukan karena seorang pemimpin transformasional diharuskan untuk memberi contoh dan motivasi kepada bawahannya sehingga perlu selalu menjaga kehormatan dan marwahnya. Dengan metode Systematic Literature Review (SLR), this research collected around 200 articles and included 10 of them in the research to answer the questions and figure out the answers. Result of this research shown that there is a little to none of research in education in Indoenesia discussed about the topic. This will lead to a wide chance for future researchers to conduct research on this topic. It is also found that face-saving will benefit the transformational leader by increasing the creativity of the followers but also showing that the transformational leader is not an anti-critique person. Meanwhile, the strategies that are applicable for the leader when she/he gets critique are contradicting, withdrawing, repairing, dan emphasizing. Keywords: face-saving, transformational leader, education